2017
DOI: 10.1155/2017/9603140
|View full text |Cite
|
Sign up to set email alerts
|

Method Validation for Progesterone Determination in Poly(methyl methacrylate) Nanoparticles Synthesized via Miniemulsion Polymerization

Abstract: Exogenous progesterone has several applications in human health and in veterinary medicine, especially in fixed-time artificial insemination protocol. Progesterone nanoencapsulation in biocompatible polymers, such as poly(methyl methacrylate) (PMMA), is an alternative to substitute silicone-based release device traditionally used for estrus control. Progesterone concentration inside the nanoparticles must be precisely known; for that reason, a validation methodology must be applied to ensure reliable results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These studies showed an enhancement of the pharmacokinetics and pharmacodynamics of the hormonal treatments, specifically, those of low molecular weight and short lifespan, such as GnRH [7,[51][52][53][54]. In addition, the opportunity to use biodegradable materials as a matrix for progesteronedelivery instead of silicon-based materials was shown [55][56][57] to sustain the release of some hormones, such as melatonin in in vitro production media [58][59][60], and to change the route of hormone administration by enhancing mucosal absorption even if these hormones have high molecular weight [35]. Overall, these studies show that the use of nano-hormone delivery systems provides many advantages to hormonal-based treatments, such as decreasing hormone dosage, changing the route of administration, increasing animal welfare, and decreasing the risk of exposition to different hormones by workers and technicians (Table 1).…”
Section: Nanotechnology Approaches For Developing Hormonal Based-trea...mentioning
confidence: 99%
“…These studies showed an enhancement of the pharmacokinetics and pharmacodynamics of the hormonal treatments, specifically, those of low molecular weight and short lifespan, such as GnRH [7,[51][52][53][54]. In addition, the opportunity to use biodegradable materials as a matrix for progesteronedelivery instead of silicon-based materials was shown [55][56][57] to sustain the release of some hormones, such as melatonin in in vitro production media [58][59][60], and to change the route of hormone administration by enhancing mucosal absorption even if these hormones have high molecular weight [35]. Overall, these studies show that the use of nano-hormone delivery systems provides many advantages to hormonal-based treatments, such as decreasing hormone dosage, changing the route of administration, increasing animal welfare, and decreasing the risk of exposition to different hormones by workers and technicians (Table 1).…”
Section: Nanotechnology Approaches For Developing Hormonal Based-trea...mentioning
confidence: 99%
“…For the SEM analysis, the samples were evenly distributed on metalized tape and inserted into the equipment at a potential of 15 kV under low vacuum 20 . For the latter, the samples were diluted (0.05% v/v), placed on copper grids (Formvar/Carbon Support Film, 100 mesh, 3.05 mm in diameter, TAAB), and coated with cathodic fluid spray to prevent sample degradation due to the electron beam 24 . TGA and DTG analyses were performed in a Netzsch STA 409PC (Netzsch Corporation, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The main matrix of these devices is composed of silicon polymers, which need to be loaded with high progesterone concentrations to release enough hormones to the vaginal mucosa. Progesterone levels into the device remain high after discard and currently, inserts based on polyethylene vinyl acetate (EVA) copolymers polyisoprene and polymethyl-methacrylate are being developed for reducing progesterone charge, thus diminishing the costs and emissions of hormones to the environment [2,42]. However, similarly to silicone-based devices, these materials are not biodegradable.…”
Section: Nano-hormone Delivery Systems and Cycle Managementmentioning
confidence: 99%
“…Oliveira and coworkers [15] developed and tested biodegradable and biocompatible nanomaterials (specifically nanofibrous mats of polylactic acid; PLA) loaded with progesterone by solution blow spinning technique, with promising results for controlled progesterone delivery. Similarly, Fogolari and coworkers [42] used a method of miniemulsion polymerization for producing two forms of progesterone-conjugated nanocapsules: nanospheres (NS) and nanocapsules (NC), using polymethyl-methacrylate, a biocompatible polymer, instead of silicone-based release devices. The encapsulation efficiencies of NS and NC were greater than 69% and 90%, with average sizes of 150-200 nm and 240-300 nm, respectively, which supports the usefulness of this method for progesterone binding.…”
Section: Nano-hormone Delivery Systems and Cycle Managementmentioning
confidence: 99%